Cognitive outcomes after cochlear implantation in older adults: A systematic review. (3rd September 2018) - Claes, Annes J.; Van de Heyning, Paul; Gilles, Annick; Van Rompaey, Vincent; Mertens, Griet
Abstract : Objectives: To critically assess the current status of the literature on cognitive outcomes after cochlear implantation in older adults. Methods: Studies were identified by searching MEDLINE (PubMed) and Cochrane Library, and checking reference lists of relevant articles. No restrictions were imposed regarding language, publication date, or publication status. Eligibility criteria were as follows: (1) the study sample included older adults aged 50 or over with severe to profound bilateral hearing loss, (2) the participants received a multi-electrode cochlear implant, and (3) a cognitive test was performed before and after implantation. Risk of bias was assessed with respect to: (A) the suitability of the cognitive tests to examine cognition in hearing-impaired (HI) subjects, (B) the control of practice effects, (C) statistical methods, and (D) other sources of bias. Results: Out of 2716 retrieved records, 6 were found eligible, examining a total of 166 patients. Five of these studies reported improvements in cognition postimplantation and one study did not observe significant changes. Control of practice effects and the statistical methods were the most common origin of observed bias. Discussion: The currently reviewed studies performed pioneering work and are indispensable for the field. However, they do not provide conclusive evidence of improved cognitive outcomes after cochlear implantation in older adults. Conclusion: Well-designed studies with long follow-up periods are imperative to verify whether cochlear implantation influences cognition in older adults. New research is stimulated to use appropriate cognitive assessment tools for HI individuals, to control for practice effects, and to perform appropriate statistical tests.